Surgical aspects of continuous ambulatory peritoneal dialisis.: Comunicación preliminar sobre 10 observaciones. - Vallverdú, Martín; Mori, Raúl; López, Daniel; Gómez Fossati, Carlos (Cirugía del Uruguay, 1987)
An evaluation of the surgical aspecls of !he collocation of peritoneal cathelers is made as regards a series of the firsl ten patients of the CAPO program from !he Nephrology Centre al !he Hospital de Clínicas